An Investigation of the Altman Z-Score Measure and Return on Equity (ROE) of Firms in the Airline Industry - Willey, Thomas; Edwards, Susan; Bhagwat, Yatin (Archives of Business Research, 2023)
This research measures the relationship between the Altman Z-Score, a measure of a firm’s financial health, and the Return on Equity (ROE), a measure of a firm’s profitability for a sample of airline companies. The period of the study covers 2014 to 2022 and uses linear regression to examine the relationship between ROE (dependent variable) and the Z-Score (independent variable). Our data set contains sixty-five (65) airline firms traded on twenty-eight (28) stock exchanges. Our initial hypothesis is that a positive and statistically significant relationship exists between the two variables over the examined period. Further research will look at the relationship in other sectors of the markets.